PENGARUH PERMAINAN BINGO MODIFIKASI VISUAL DALAM MENINGKATKAN KEMAMPUAN BERHITUNG ANAK DITAMAN KANAK-KANAK IQRA - Laila Kusuma, Zulminiati; Nurhafizah, Mutia Afnida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study is motivated by the problem that children's counting skills are not well developed. some children have been able to mention the numbers 1-20 but when asked to match with the number symbol the child has not been able to show correctly, besides that there is still a lack of availability of varied learning media, and a lack of teacher creativity in creating media to improve counting skills in children. Thus, bingo games are employed as a means to enhance children's counting skills, allowing them to grasp counting ideas through engaging and enjoyable activities. The purpose of this research is to find out if playing bingo games improves the counting skills of kindergarteners at Iqra. This study employed a quantitative strategy based on a quasi-experimental design. Using a purposive sampling strategy, a total of ten students from two different classes class B2 (the experimental group) and class B1 (the control group) made up the population of this study. Statement sheets were utilized as data collecting tools, and methods for data analysis included tests for normality, homogeneity, and hypothesis testing, as well as oral and action tests. After that, SPSS 30.0 was used to conduct the difference test (t-tests). After the test, the average value in the experimental group rose from 13.00 to 18.90, according to the data.